Spontaneous Clearance of Hepatitis B Surface Antigenemia After Long‐term Hemodialysis. Issue 1 (17th October 2013) - Patel, Chinmay; Monga, Divya; Alexander, Mohini; Magoon, Sandeep; Bernstein, David; Wagner, John D.; Mattana, Joseph; Rodby, Roger A.
Abstract Persistent infection with the hepatitis B virus (HBV) [as indicated by chronic HBV surface antigenemia (HBsAg)] continues to be an important problem in end‐stage renal disease (ESRD) patients and specifically in those receiving maintenance hemodialysis (HD). Patients on HD who are HBsAg‐positive for a year have little chance of ever eliminating the virus; hence, clearance of HBsAg is a rare event in long‐term HD patients. We report the case of a 62‐year‐old diabetic woman who was HBsAg‐positive at the time she started HD and remained so until 10 years later when she became HBsAg‐negative followed by the development of hepatitis B surface antibody (anti‐HBs). Prior to her seroconversion, she suffered a persistent infection of her HD arteriovenous graft (AVG) that required prolonged antibiotics and several surgical procedures. We speculate that this immune stimulation contributed to her seroconversion.